Corrosion Fatigue of Friction Stir Welded Magnesium Alloy AZ31B: A Comparative Study - Tapp, Daniel C. (My University, 2017)
Load controlled cyclic fatigue testing was conducted on base metal (BM) and friction stir welded (FSW) magnesium (Mg) alloy AZ31B compact tension (CT) specimens in laboratory air and a 0.05 wt. % NaCl fog environment in efforts to delineate the effects of salt fog and stir welding on fatigue performance under tension-tension loading conditions. FSW beads were produced on single piece AZ31B sheet product, simulating a pristine friction stir butt weld. Optical and electron microscopy, as well as X-ray diffraction was employed to observe the features and characteristics of fracture surfaces. The resulting stress vs. number of cycles to failure (S-N) curves demonstrated a reduction in fatigue life in a salt fog environment and an increase in fatigue life for FSW specimens compared to equivalently loaded BM specimens. Tensile frame displacement data indicated that the salt fog environment had an immediate effect on the BM samples, with an increased displacement required to meet the load control criteria. Fatigue cracks that propagated in CT samples that were notched in the direction of FSW tool travel consistently propagated towards the retreating side (RS) of the stir zone.
Keywords: Magnesium; Corrosion; Fatigue; Friction Stir Welding